2008
DOI: 10.1021/jm8006257
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Delivery of Glycan-Based Paclitaxel Prodrugs to Cancer Cells via Glucose Transporters

Abstract: This report describes the synthesis of four novel paclitaxel based prodrugs with glycan conjugation (1-4). Glycans were conjugated using an ester or ether bond as the linker between 2'-paclitaxel and the 2'-glucose or glucuronic acid moiety. These prodrugs showed good water solubility and selective cytotoxicity against cancer cell lines, but showed reduced toxicity toward normal cell lines and cancer cell lines with low expression levels of GLUTs. The ester conjugated prodrug 1 showed the most cytotoxicity amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 41 publications
3
79
0
Order By: Relevance
“…Thus, structural modification of podophyllotoxin for developing new antitumor drugs with increased selectivity and reduced toxicity is highly desirable. In recent years, the altered glucose metabolism in cancer cells has been explored for targeted cancer therapy [18]. Glucose is the main source of metabolic energy of animal cells, generating ATP through glycolysis and oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, structural modification of podophyllotoxin for developing new antitumor drugs with increased selectivity and reduced toxicity is highly desirable. In recent years, the altered glucose metabolism in cancer cells has been explored for targeted cancer therapy [18]. Glucose is the main source of metabolic energy of animal cells, generating ATP through glycolysis and oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting compound, whose transport was mediated at least in part by GLUT1 as confirmed by fluorescence microscopy studies, showed improved pharmaceutical properties and a comparable cytotoxicity against MCF-7 breast cancer cells without toxicity on normal cells, but it showed a reduced toxicity on most of the tested cancer cell lines compared to the parent compound. 90 …”
Section: Sugar-conjugate Compounds Interacting With Glutsmentioning
confidence: 99%
“…Paclitaxel is an important agent in the treatment of several cancers including breast cancer. Glucoseconjugated paclitaxel derivatives through the ester bond or the ether bond ( Figure 3) were transported into cells against tumor cell lines such as NCI-H838 (lung adenocarcinoma), MES-SA (uterine carcinoma), HCT-116 (colon carcinoma), and NPC-TW01 (nasopharyngeal carcinoma) with the exception of breast cancer cells, based on Glut1-mediated transport, and then exhibited the cytotoxic activity [15]. Similarly, it is suggested that glucose-conjugated paclitaxel derivatives can be transported into breast cancer cells and exhibit the cytotoxic activity there, because GluT1 is overexpressed even in breast cancer cells.…”
Section: Implementation Of Transporter-conscious Designmentioning
confidence: 99%